Participatory Democracy in India - Shreepad R Malagi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Abstract: Participatory democracy in India represents an evolving democratic ethos where citizens play a direct and active role in the decision-making processes beyond periodic elections. Rooted in the principles of decentralization and inclusion, participatory democracy seeks to empower people at the grassroots level through mechanisms like Gram Sabhas, local self-governance institutions (Panchayati Raj), public consultations, and social audits. India’s constitutional framework, particularly the 73rd and 74th Amendments, institutionalized this democratic model by devolving power and resources to local bodies. Despite significant strides, challenges such as political apathy, lack of awareness, bureaucratic hurdles, and socio-economic inequalities continue to hinder effective participation. However, digital platforms, civil society movements, and increased civic engagement are reshaping democratic participation in contemporary India. This paper explores the historical evolution, institutional frameworks, key practices, challenges, and future prospects of participatory democracy in India, emphasizing its critical role in deepening democratic governance and ensuring accountability and inclusiveness.